2020
DOI: 10.1371/journal.pone.0231348
|View full text |Cite
|
Sign up to set email alerts
|

Halotolerant rhizobacteria Pseudomonas pseudoalcaligenes and Bacillus subtilis mediate systemic tolerance in hydroponically grown soybean (Glycine max L.) against salinity stress

Abstract: Salt stress is one of the devastating factors that hampers growth and productivity of soybean. Use of Pseudomonas pseudoalcaligenes to improve salt tolerance in soybean has not been thoroughly explored yet. Therefore, we observed the response of hydroponically grown soybean plants, inoculated with halotolerant P. pseudoalcaligenes (SRM-16) and Bacillus subtilis (SRM-3) under salt stress. In vitro testing of 44 bacterial isolates revealed that four isolates showed high salt tolerance. Among them, B. subtilis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 71 publications
3
42
0
1
Order By: Relevance
“…We found that the RWC content of B. clausii treated plants was higher in stressed and non-stressed conditions which indicates that this strain was able to limit the advancement of a fungal pathogen in the plant body. Moreover, it also helped the plants to retain the water content necessary for proper functioning as indicated by previous studies regarding RWC of plants subjected to various types of stresses [24,57].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…We found that the RWC content of B. clausii treated plants was higher in stressed and non-stressed conditions which indicates that this strain was able to limit the advancement of a fungal pathogen in the plant body. Moreover, it also helped the plants to retain the water content necessary for proper functioning as indicated by previous studies regarding RWC of plants subjected to various types of stresses [24,57].…”
Section: Discussionmentioning
confidence: 89%
“…Proline is an amino acid that plays a beneficial role in plants against biotic and abiotic stresses. It is an efficient osmolyte and besides this, it also plays other significant roles in stressed plants, i.e., it acts as an antioxidant molecule, signaling molecule, and a metal chelator [24,60]. The results for the proline contents of charcoal rot stressed plants were more pronounced in the case of B. clausii treated plants as compared to that of P. putida.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In a study it was shown that HT-PGPR Bacillus subtilis reduced the absorption of Na + by Arabidopsis thaliana roots through down-regulation of high-affinity K + transporter (HKT1) in salt-affected conditions [41] . Yasmin et al [45] revealed that inoculation of salt-stressed soybean plants with Pseudomonas pseudoalcaligenes triggered synthesis of key defense enzymes that reduced the Na + concentration in roots and shoots simultaneously balancing the cellular condition by increasing intracellular K + levels. Similarly, Pseudomonas koreensis strain AK-1 reduced Na + and elevated K + levels in Glycine max L. Merrill [46] .…”
Section: Ht-pgpr Mediated Salt Tolerance In Plantsmentioning
confidence: 99%